Cytokine Secretion, Viability, and Real-Time Proliferation of Apical-Papilla Stem Cells Upon Exposure to Oral Bacteria - Rakhimova, Olena; Schmidt, Alexej; Landström, Maréne; Johansson, Anders; Kelk, Peyman; Romani Vestman, Nelly (Frontiers in Cellular and Infection Microbiology, 2021)
The use of stem cells from the apical papilla (SCAPs) has been proposed as a means of promoting root maturation in permanent immature teeth, and plays a significant role in regenerative dental procedures. However, the role of SCAPs may be compromised by microenvironmental factors, such as hypoxic conditions and the presence of bacteria from infected dental root canals. We aim to investigate oral bacterial modulation of SCAP in terms of binding capacity using flow cytometry and imaging, real-time cell proliferation monitoring, and cytokine secretion (IL-6, IL-8 and TGF-β isoforms) under anaerobic conditions. SCAPs were exposed to key species in dental root canal infection, namely Actinomyces gerensceriae, Slackia exigua, Fusobacterium nucleatum and Enterococcus faecalis, as well as two probiotic strains, Lactobacillus gasseri strain B6 and Lactobacillus reuteri (DSM 17938). We found that A. gerensceriae, S. exigua, F. nucleatum, and E. faecalis, but not the Lactobacillus probiotic strains bind to SCAPs on anaerobic conditions. E. faecalis and F. nucleatum exhibited the strongest binding capacity, resulting in significantly reduced SCAP proliferation. Notably, F. nucleatum, but not E. faecalis, induce production of the proinflammatory chemokine IL-8 and IL-10 from SCAPs. Production of TGF-β1 and TGF-β2 by SCAPs was dependent on species, cell line, and time, but secretion of TGF-β3 did not vary significantly over time. In conclusion, SCAP response is compromised when exposed to bacterial stimuli from infected dental root canals in anaerobic conditions. Thus, stem cell-mediated endodontic regenerative studies need to include microenvironmental conditions, such as the presence of microorganisms to promote further advantage in the field.